The Changing Face of in vitro Culture Models for Thyroid Cancer Research: A Systematic Literature Review - Chew, Dylan; Green, Victoria; Riley, Andrew; England, Richard James; Greenman, John (Frontiers in Surgery, 2020)
Background Thyroid cancer is the most common endocrine malignancy worldwide. Since the 1950s, in vitro thyroid culture systems have been used in thyroid cancer research. In vitro culture models have evolved from 2-dimensional thyrocyte monolayers into physiologically functional 3-dimensional organoids. Recently, research groups have utilised in vitro thyroid cancer models to identify numerous genetic and epigenetic factors that are involved with tumorigenesis as well as test the efficacy of cytotoxic drugs on thyroid cancer cells and identify cancer stem cells within thyroid tumours. The objective of this literature review is to summarise how thyroid in vitro culture models have evolved and highlight how in vitro models have been fundamental to thyroid cancer research. Search Strategy The National Institute for Health and Care Excellence (NICE) Healthcare and Databases Advanced Search (HDAS) tool was used to search EMBASE, Medline and PubMed databases. The search period was confined from January 2008 until June 2019. A manual search of the references of review articles and other key articles was also performed using Google Scholar. Evaluation Method All experimental studies and review articles that explicitly mentioned the use of in vitro models for thyroid cancer research in the title and/or abstract were considered. Full-text versions of all selected articles were evaluated. Experimental studies were reviewed and grouped according to topic: genetics/epigenetics, drug testing/cancer treatment and side populations (SP)/tumour microenvironment (TME). Results 3373 articles were identified through database and manual searches. 1216 articles remained after duplicates were removed. 589 articles were excluded based on title and/or abstract. Of the remaining 627 full-text articles: 24 were review articles, 332 related to genetic/epigenetics, 240 related to drug testing/treatments, and 31 related to SP/TME. Conclusion In vitro cell culture models have been fundamental in thyroid cancer research. There have been many advances in culture techniques- developing complex cellular architecture that more closely resemble tumours in vivo. Genetic and epigenetic factors that have been identified using in vitro culture models can be used as targets for novel drug therapies. In the future, in vitro systems will facilitate personalised medicine, offering bespoke treatments to patients.